Determination of the Chronological Age of Skull Base Suture Closure Using Computed Tomography - Lingawi, Sattam S. (Journal of Basic & Applied Sciences, 2012)
The aim of this study was to determine the postnatal chronological age of central and posterior skull base suture closure using computed tomography. The central and posterior skull base suture of pediatric brain CT’s obtained from 75 girls and 125 boys of varying ages (newborn to 18 years) were evaluated for this purpose. Premature infants of less than 38 weeks gestation, cases of congenital skull base malformations, and cranial anomalies were excluded. All brain CT studies were performed using 3 mm axial slice thickness at the skull base level. The central and posterior skull base sutures, synchondroses and ossification centers were all assessed for normal appearance and age of closure. The age of initial and completed fusion for the 12 main sutures in the occipital and sphenoid bones, were determined. Data obtained during the study provides CT scans standard for normal age of closure of the central and posterior skull base sutures that may assist in the future evaluation of skull base fractures, dysplasia and deformities.